PEMBIAYAAN DANA TALANGAN HAJI PASCA PMA No.24 TAHUN 2016 DALAM PERSEPEKTIF MASLAHAH MURSALAH DAN SADD ADZ-DZARI'AH: Dana Talangan Haji - ulie, Minati Maulida (Institut Agama Islam Darul Ulum Kandangan, 2021)
The Hajj bailout is a solution for some Muslims who cannot cover the cost of Hajj in cash, with this Hajj bailout many people are interested in registering for Hajj and immediately getting a Hajj portion number as a form of certainty of departure to the holy land. Kospin Jasa Syari'ah issued a Hajj bailout financing product, this product is used to help people who do not have enough money to meet the costs of the pilgrimage. Over time, with the Regulation of the Minister of Religion of the Republic of Indonesia Number: 24 of 2016 stipulating that Banks Receiving Deposits for Hajj Organizing Fees (BPS-BPIH) are prohibited from providing Hajj bailout funds, either directly or indirectly. This raises legal issues related to the practice of financing hajj bailouts at Kospin Jasa Syari'ah which is reviewed from the perspective of maslahah mursalah and sadd adz-dzari'ah. This research is a type of field research that uses descriptive analysis method. The purpose of this study is to find out how the financing of the hajj bailout product at the JASA Syari'ah kospin, then how to analyze the maslahah mursalah and sadd adz-dzari'ah on the hajj bailout funds. In its implementation, the contract used in the Hajj bailout product of Kospin Jasa Syari'ah is a multi-service Ijarah contract with two systems, namely the Ijarah contract with the term system and the Ijarah contract with the installment system in collaboration with Bank Muamalat Indonesia, the Pekalongan branch. The existence of PMA No. 24 of 2016 when analyzed with the theory of maslahah mursalah and Sadd adz-dzari'ah shows that the prohibition of hajj bailout funds must really be implemented because it follows the needs of the community at this time.